Allogeneic stem cell transplantation in patients with atypical chronic myeloid leukaemia: a retrospective study from the Chronic Malignancies Working Party of the European Society for Blood and Marrow Transplantation - Onida, Francesco; De Wreede, Lliesbeth C.; van Blezan, Anja; Elkema, Diderik-Jan; Byrne, Jenny L.; Iori, Anna P.; Schots, Rick; Jungova, Alexandra; Schetelig, Johannes; Finke, Juergen; Veelken, Hendrick; Johanssen, Jan-Erik; et al. (Wiley, 2017)
Atypical chronic myeloid leukaemia (aCML) is an aggressive malignancy for which allogeneic haematopoietic stem cell transplantation (allo-HSCT) represents the only curative option. We describe transplant outcomes in 42 patients reported to the European Society for Blood and Marrow Transplantation (EBMT) registry who underwent allo-HSCT for aCML between 1997 and 2006. Median age was 46 years. Median time from diagnosis to transplant was 7 months. Disease status was first chronic phase in 69%. Donors were human leucocyte antigen (HLA)-identical siblings in 64% and matched unrelated (MUD) in 36%. A reduced intensity conditioning was employed in 24% of patients. T-cell depletion was applied in 87% and 26% of transplants from MUD and HLA-identical siblings, respectively. According to the EBMT risk-score, 45% of patients were ‘low-risk’, 31% ‘intermediate-risk’ and 24% ‘high-risk’. Following allo-HSCT, 87% of patients achieved complete remission. At 5 years, relapse-free survival was 36% and non-relapse mortality (NRM) was 24%, while relapse occurred in 40%. Patient age and the EBMT score had an impact on overall survival. Relapse-free survival was higher in MUD than in HLA-identical sibling HSCT, with no difference in NRM. In conclusion, this study confirmed that allo-HSCT represents a valid strategy to achieve cure in a reasonable proportion of patients with aCML, with young patients with low EBMT risk score being the best candidates.